Comparative Study on the Electrical and Thermal Performance Efficiencies of Film Water-Cooled Solar Photovoltaic Modules - Ahmad, Abubakar (Universitas Pendidikan Mandalika, 2026)
High operating temperature remains a major factor limiting the outdoor performance of solar photovoltaic (PV) modules, particularly in hot climatic regions. This study aimed to determine the solar input and output power and heat of PV modules under natural air-cooling and film water-cooling conditions, to evaluate the corresponding electrical and thermal performance efficiencies, and to compare the relative performance gains achieved by film water-cooling. The experiment was conducted in Sokoto, Nigeria, using two identical PV modules operated simultaneously under natural air-cooling and film water-cooling conditions. Outdoor measurements were taken from 8:30 am to 5:00 pm over five consecutive days. Solar irradiance, voltage, current, module temperature, water temperature, ambient temperature, and wind speed were measured, and the recorded data were used to calculate solar input and output power and heat, as well as electrical and thermal efficiencies. The results showed a clear diurnal variation in solar input, with peak irradiance, input power, and input heat of 605.2 W/m², 484.2 W, and 242.2 J, respectively, recorded at 12:30 pm. The film water-cooled module generally exhibited higher output power and output heat than the naturally air-cooled module during most observation intervals. Electrical efficiency ranged from 6.22% to 10.52% for the film water-cooled module and from 5.90% to 8.52% for the naturally air-cooled module. Thermal efficiency ranged from 18.82% to 70.64% for the film water-cooled module, compared with 19.26% to 41.16% for the naturally air-cooled module. Overall, film water-cooling improved the electrical and thermal response of the PV module under the tested hot-climate conditions, with the strongest benefit observed during periods of higher solar loading.